Historia del programa radial “pedagógicamente” - Galindo Mendoza, Myriam Cristina; Aragón Bueno, María Gracia (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This article is a review that aims to reveal the experience that has been carried out since the beginning of the radio program that belongs to the Bachelor in Basic Edu- cation with emphasis on Mathematics, Humanities and Spanish Language of the Faculty of Distance Studies at Universidad Pedagógica y Tecnológica de Colombia, which is called “Pedagogically”. This program recognizes the several possibilities of the radio as an opportunity that provides the social appropriation of knowledge by means of dissemination and continuous communication about topics of edu- cational and formative interest. This radial space has been an important input to generate reflection about environmental issues, to rescue academic processes as an opportunity to enrich, highlight, portrait meaningful experiences and proposals of students, graduates of the degree and experts in several subjects concerning education; in this way it has been possible to make a contribution to the pedagogical construction for the program.